Adaptation and Preliminary Testing of an Intervention to Reduce Stigma among Individuals Living with HIV in the Deep South. Issue 1 (2nd January 2022) - Reif, Susan; Rao, Deepa; Wilson, Elena; Beckwith, Nicole; Frey, Sarah; Cooper, Haley; Ward, Dafina; Belden, Micha
ABSTRACT: HIV-related stigma has been implicated as a contributor to the disproportionate impact of HIV in the US Deep South. However, effective interventions aimed at reducing HIV-related stigma are limited in the region. This study adapted and piloted an HIV-related stigma reduction intervention, the UNITY Workshop, for use among people living with HIV in the Deep South following a modified framework of the ADAPT-ITT model and the five principles of Corrigan's Model of Strategic Stigma Change. The adapted intervention, named the YOUNITY Workshop, was conducted in an experiential, group format and focused on enhancing stigma coping skills. Workshop satisfaction was high, and most participants reported acquiring new skills for coping with HIV-related stigma and HIV status disclosure. Participants also reported benefitting from the social support generated from the workshop and desired additional opportunities to connect with others in the future. This pilot study demonstrated the feasibility and positive preliminary outcomes of conducting a group-based HIV stigma reduction workshop in the Deep South. Future rigorous testing of the YOUNITY Workshop is planned to better examine health outcomes associated with participation.